Adição de vermiculita expandida mícron em pastas de baixa densidade para cimentação de poços de petróleo - Nunes, Eduardo Raimundo Dias (2010)
The northeastern region of Brazil has a large number of wells producing oil using a method of secondary recovery steam injection, since the oil produced in this region is essentially viscous. This recovery method puts the cement / coating on thermal cycling, due to the difference in coefficient of thermal expansion between cement and metal coating causes the appearance of cracks at this interface, allowing the passage of the annular fluid, which is associated with serious risk socioeconomic and environmental. In view of these cracks, a correction operation is required, resulting in more costs and temporary halt of production of the well. Alternatively, the oil industry has developed technology for adding new materials in cement pastes, oil well, providing high ductility and low density in order to withstand the thermo-mechanical loads generated by the injection of water vapor. In this context, vermiculite, a clay mineral found in abundance in Brazil has been applied in its expanded form in the construction industry for the manufacture of lightweight concrete with excellent insulation and noise due to its high melting point and the presence of air in their layers lamellar. Therefore, the vermiculite is used for the purpose of providing low-density cement paste and withstand high temperatures caused by steam injection. Thus, the present study compared the default folder containing cement and water with the folders with 6%, 8% and 10% vermiculite micron conducting tests of free water, rheology and compressive strength where it obtained the concentration of 8 % with the best results. Subsequently, the selected concentration, was compared with the results recommended by the API standard tests of filtered and stability. And finally, analyzed the results from tests of specific gravity and time of thickening. Before the study we were able to make a folder with a low density that can be used in cementing oil well in order to withstand the thermo-mechanical loads generated by steam injection